2019
DOI: 10.22161/ijeab/4.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Physicochemical Analysis of Water from Different Sources

Abstract: Introduction: Water is one of the important natural sources for all living organisms. It is one of the ecological systems. It's the essential source for human health, food production and economic development. The quality of water is important is an important parameter to be noted. The quality of water is affected by various contaminants. The consumption of contaminated water may cause serious health problems due to the activity of microorganism present in it .Due to the activity of microorganism the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Water is one of the most important and abundant compounds of the ecosystem [1,2,3]. It is the most vital element among the natural resources [4,5,6,7], and is critical for the survival of all living organisms including human, food production, and economic development. Also, Saeed and Mahmoud [8] reported that, importance of water in our day-to-day activities makes it necessary for thorough analysis to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Water is one of the most important and abundant compounds of the ecosystem [1,2,3]. It is the most vital element among the natural resources [4,5,6,7], and is critical for the survival of all living organisms including human, food production, and economic development. Also, Saeed and Mahmoud [8] reported that, importance of water in our day-to-day activities makes it necessary for thorough analysis to be conducted.…”
Section: Introductionmentioning
confidence: 99%